AKULTURASI BUDAYA MELAYU DALAM TERJEMAH AL QURAN (Studi Signifikansi Bahasa al-Quran Terjemahan terhadap Pemahaman Islam di Sumatera Selatan) - Anisatul Mardiah (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2018)
Acculturation can also be called the process of spreading culture or cultural transmission in process. In disseminating the contents of the al-Quran among Muslims who are not Arabic, translation is certainly a necessity that must be fulfilled. Al-Quran translation in nusantara Indonesia has been going on since the 17th century. Beginning with Hamzah Fansuri, an ulama of Aceh, in the following period, the al-Quran was translated into various regional languages as well as Malay. Translation also became the main transmission line of the al-Quran to have direct dialogue with non-Arab Muslims, which turned out to be able to bring people towards advanced and more valuable civilizations. Especially in the South Sumatra region, the spread of the al-Quran and its translation in local languages made the ummah closer to the teachings of Islam. In the end, it was difficult to distinguish between acculturation and assimilation of Islam in various Malay customs and cultures in all areas of human life, because at the peak of the Malay slogan based on Shari'ah, Shari'ah based on the Koran and Hadith, is a real picture of the Malay of South Sumatr’s life pattern based on Islam.